Pembentukan Instrumen Hukum Internasional Baru tentang Lalu Lintas Di Ruang Angkasa - Prasetyo, Dony Aditya (DIVERSI : Jurnal Hukum, 2023)
This research aims to discuss the regulation of space traffic based on the existing space law. Activity in space is becoming massive every year. Currently state and non-state entities are competing to carry out activities in outer space. It causes space is getting crowded, and it is feared that it will cause problems in the future. The research purpose is to describe the existing rules of space law related to the massive activities in space and to analyze the need for international law rules regarding space traffic. The type of research used is normative research. The research results revealed that the current state's activities in space do not pay attention to the provisions regarding state activities in space. It should not interfere with the other countries activities because the existing rules are unclear. So it is necessary to develop clearer rules of international law regarding space traffic.